High Risk of Clinical Relapse in Patients With Chronic Hepatitis B Virus Infection After Cessation of Prophylactic Antiviral Therapy for Rituximab-Containing Chemotherapy. (12th May 2020) - Chang, Wei-Yuan; Chiu, Yen-Cheng; Chiu, Fang-Wei; Hsu, Yao-Chun; Tseng, Tai-Chung; Cheng, Pin-Nan; Yang, Sheng-Shun; Liu, Chun-Jen; Su, Tung-Hung; Yang, Hung-Chih; Liu, Chen-Hua; Chen, Pei-Jer; et al.
Abstract: Background: Prophylaxis with nucleos(t)ide analogue (NA) is recommended to prevent hepatitis B virus (HBV) reactivation in hepatitis B surface antigen (HBsAg)–positive patients receiving rituximab-based B-cell depletion therapy. However, little is known about the risk of clinical relapse after withdrawal of NA. Methods: We retrospectively analyzed 77 noncirrhotic HBsAg carriers with hematological cancer who received rituximab-containing chemotherapy. All of them received either prophylactic entecavir or tenofovir therapy. The risk of clinical relapse and hepatic decompensation after cessation of NA was explored. Results: Clinical relapse and hepatic decompensation developed in 25 (32.5 %) and 11 (14.3 %) of the patients, respectively, and 2 patients died of hepatic decompensation. Most of the hepatic events occurred within 1 year (20 of 25; 80.0%) after stopping NA. A higher pretreatment viral load (≥2000 vs <2000 IU/mL) was associated with increased risks of clinical relapse (hazard ratio, 3.47; 95% confidence interval, 1.56–7.73) and hepatic decompensation (9.91; 2.14–45.92). Of 51 patients with pretreatment viral load <2000 IU/mL, clinical relapse occurred in 10 (19.6 %) and hepatic decompensation in 2 (3.9%). Conclusions: Pretreatment HBV DNA ≥2000 IU/mL is associated with increased risk of liver-related disease after cessation of prophylactic NA therapy in patients who received rituximab-containing chemotherapy. Abstract : In a multicenter study of 77 hepatitis B surface antigen carriers with hematological cancer who received rituximab-containing chemotherapy, high risks of clinical relapse and hepatic decompensation were noted after cessation of prophylactic antiviral treatment. Pretreatment hepatitis B virus DNA level of 2000 IU/mL was effective to stratify the risks.